1995
DOI: 10.1080/13803399508406588
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative features of the memory deficit associated with hiv infection and AIDS: Cross-validation of a discriminant function classification scheme

Abstract: The neuropsychological defects associated with late stage HIV infection and AIDS have been characterized as being similar to those seen in patients with dementia syndromes of subcortical etiologies. The purpose of this paper is to report on the cross-center replication of the classification of HIV-infected subjects' neuropsychological status based on a discriminant function generated from other HIV-related and unrelated cognitively impaired subjects. Of the HIV-control subjects, 42/46 (91.3%) were classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 21 publications
5
38
0
Order By: Relevance
“…The similarity between HIV-D and HD in benefits from retrieval cues suggests that the remote memory impairment involved is due in part to a retrieval deficit and, furthermore, that remote memory impairment in HIV-D may be largely mediated by subcortical pathology (Navia et al, 1986), as appears to be the case in HD (Becker et al, 1997;Peavy et al, 1994;White et al, 1997). However, the inability of the HIV-D and HD groups to benefit from cuing to the same degree as the YHC group suggests that another factor, such as loss of remote memory, may also contribute to the RA pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity between HIV-D and HD in benefits from retrieval cues suggests that the remote memory impairment involved is due in part to a retrieval deficit and, furthermore, that remote memory impairment in HIV-D may be largely mediated by subcortical pathology (Navia et al, 1986), as appears to be the case in HD (Becker et al, 1997;Peavy et al, 1994;White et al, 1997). However, the inability of the HIV-D and HD groups to benefit from cuing to the same degree as the YHC group suggests that another factor, such as loss of remote memory, may also contribute to the RA pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively mild, non-temporally graded RA associated with HIV-D and HD may be indicative of a general retrieval deficit that equally affects recall of information from any past time period. Such a retrieval deficit has been postulated as a contributory factor in the anterograde memory deficit observed with HIV-D or HD (Becker et al, 1997;Butters, Wolfe, Martone, Granholm, & Cermak, 1985;White et al, 1997; for a review, see Paulsen & Robinson, 2001) and has been attributed to the frontostriatal dysfunction that characterizes these disorders. In contrast, the severe and temporally graded RA associated with AD may reflect the interruption of a long-term consolidation process that is dependent on medial temporal lobe structures such as the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in HIV-1 infection may be limited due to shortcomings associated with the characterization of memory profiles in terms of a strict "subcortical" versus "cortical" distinction (Becker et al, 1995;Delis et al, 1995;Peavy et al, 1994;White et al, 1997). There is evidence in the literature to support the existence of multiple memory systems linking frontal and subcortical regions (Crosson, 1992;Cummings, 1993a;Lichter & Cummings, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of CVLT profiles of individuals with HIV-1 infection have reported that the pattern of verbal memory performance is characteristic of predominant subcortical dysfunction (Becker et al, 1995;Delis et al, 1995;Peavy et al, 1994;White et al, 1997). Specifically, CVLT profiles (impaired learning and recall, intact retention, ability to benefit from recognition testing relative to recall) are thought to be indicative of a retrieval deficit in a subgroup of individuals with HIV-1 infection0AIDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation